Organizational culture and its impact on employee performance - Ditta Desiani Hanifah; Rofi Rofaida; Annisa Ciptagustia (Human Resource Management Studies, 2021)
This research is motivated by problems related to the decline in the performance of employees of PT. Urbane Indonesia in 2016- 2017. With the declining performance of employees at PT. Urbane Indonesia, if left unchecked, will have a negative impact on the company. Of the many factors that affect employee performance, what attracts researchers is organizational culture. The purpose of the study was to determine the effect of organizational culture on employee performance at PT. Urbane Indonesia, to know the description of Organizational Culture at PT. Urbane Indonesia and to determine the level of employee performance at PT. Urbane Indonesia. This study uses descriptive and verification methods with a population of 67 employees and a sample of 67 employees. The analysis technique used is simple linear regression analysis. Hypothesis testing using t-test. The results of this study can be seen that the organizational culture together has a positive and significant effect on employee performance.